Genetically Engineered Bacterial Ghosts as Vaccine Candidates Against Klebsiella pneumoniae Infection - Svetlana V. Dentovskaya; Anastasia S. Vagaiskaya; Alexandra S. Trunyakova; Alena S. Kartseva; Tatiana A. Ivashchenko; Vladimir N. Gerasimov; Mikhail E. Platonov; Victoria V. Firstova; Andrey P. Anisimov (Vaccines)
Background/Objectives Bacterial ghosts (BGs), non-living empty envelopes of bacteria, are produced either through genetic engineering or chemical treatment of bacteria, retaining the shape of their parent cells. BGs are considered vaccine candidates, promising delivery systems, and vaccine adjuvants. The practical use of BGs in vaccine development for humans is limited because of concerns about the preservation of viable bacteria in BGs. Methods: To increase the efficiency of Klebsiella pneumoniae BG formation and, accordingly, to ensure maximum killing of bacteria, we exploited previously designed plasmids with the lysis gene E from bacteriophage φX174 or with holin–endolysin systems of λ or L-413C phages. Previously, this kit made it possible to generate bacterial cells of Yersinia pestis with varying degrees of hydrolysis and variable protective activity. Results: In the current study, we showed that co-expression of the holin and endolysin genes from the L-413C phage elicited more rapid and efficient K. pneumoniae lysis than lysis mediated by only single gene E or the low functioning holin–endolysin system of λ phage. The introduction of alternative lysing factors into K. pneumoniae cells instead of the E protein leads to the loss of the murein skeleton. The resulting frameless cell envelops are more reminiscent of bacterial sacs or bacterial skins than BGs. Although such structures are less naive than classical bacterial ghosts, they provide effective protection against infection by a hypervirulent strain of K. pneumoniae and can be recommended as candidate vaccines. For our vaccine candidate generated using the O1:K2 hypervirulent K. pneumoniae strain, both safety and immunogenicity aspects were evaluated. Humoral and cellular immune responses were significantly increased in mice that were intraperitoneally immunized compared with subcutaneously vaccinated animals (p < 0.05). Conclusions: Therefore, this study presents novel perspectives for future research on K. pneumoniae ghost vaccines.